2015
DOI: 10.1111/apa.13141
|View full text |Cite
|
Sign up to set email alerts
|

Children with cerebral palsy do not achieve healthy physical activity levels

Abstract: Mobile phone 0046 70 395 90 01 2 ABSTRACT Aim: This study compared daily activity energy expenditure (AEE) in children with cerebral palsy with a control group and investigated whether the children achieved healthy levels of physical activity. Methods:We enrolled eight children with bilateral cerebral palsy, from eight to 10 years of age, and a group of controls matched for age and gender. For three days physical activity was simultaneously measured by accelerometers and self-reports using a diary. The daily A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…84 This was similar to that reported among Dutch adults with CP (20.9%). 83 Twenty-two studies assessed participation in physical activity among people with CP, 35,83,94,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] most of which (54.5%) only included people who walked independently with or without a walking aid. 83 Twenty-two studies assessed participation in physical activity among people with CP, 35,83,94,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] most of which (54.5%) only included people who walked independently with or without a walking aid.…”
Section: Modifiable Behavioural Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…84 This was similar to that reported among Dutch adults with CP (20.9%). 83 Twenty-two studies assessed participation in physical activity among people with CP, 35,83,94,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] most of which (54.5%) only included people who walked independently with or without a walking aid. 83 Twenty-two studies assessed participation in physical activity among people with CP, 35,83,94,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] most of which (54.5%) only included people who walked independently with or without a walking aid.…”
Section: Modifiable Behavioural Risk Factorsmentioning
confidence: 99%
“…83 Approximately 49% of Dutch adults with CP reported consuming alcohol, which was lower than the general population. [101][102][103][104][105][106][107][108][111][112][113][114] There was 16 not applicable to any of the objectives of the review 8 did not report results for people with CP separately 8 did not include people with CP 2 not an original research report 1 a second report of a study already included 13 records identified by reviewing reference lists [101][102][103][104][105][106][107][108][111][112][113][114] There was 16 not applicable to any of the objectives of the review 8 did not report results for people with CP separately 8 did not include people with CP 2 not an original research report 1 a second report of a study already included 13 records identified by reviewing reference lists …”
Section: Modifiable Behavioural Risk Factorsmentioning
confidence: 99%
“…As such they are one important basis for habilitation interventions because they are crucial for participation in daily life and society [24,25]. Physical activity in leisure time, as well as physical education in school, is crucial to enhance function and maintain health [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity in leisure time, as well as physical education in school, is crucial to enhance function and maintain health [26,27]. Studies show that according to the Nordic recommendations of nutrition [26], children with CP do not have adequate physical activity, and their level of leisure activity decreases with age [6,24,28]. …”
Section: Introductionmentioning
confidence: 99%
“…), varying through periods of rest, work, and leisure . Children and young people with cerebral palsy (CP) compared with typically developing peers have lower levels of HPA by, on average 2092 kilojoules per 24 hours . A cross‐sectional study of 62 children with CP aged 7 to 13 years using activity monitors in free‐living conditions found they were less active on the weekend than on weekdays .…”
mentioning
confidence: 99%